1993
DOI: 10.1021/om00034a018
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic compounds of Group III. 52. Active sites for ethylene polymerization with titanium(IV) catalysts in homogeneous media: multinuclear NMR study of ion-pair equilibria and their relation to catalyst activity

Abstract: By means of a multinuclear NMR study of the complexes formed between AlC13 and either CpZTiClz or CpzTi(CHzSiMe3)Cl in chloroalkane solution, isomeric forms of the resulting 1:l complexes have been detected. The influence of temperature, concentration, ratio of the titanocene chloride to aluminum chloride, and the nature of the solvent upon the 'H, 13C, and 27Al NMR spectra has been investigated. The spectral changes caused by the foregoing factors give compelling evidence for an equilibrium in such CpzTi(R)Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 102 publications
(41 citation statements)
references
References 0 publications
2
38
0
1
Order By: Relevance
“…Shilov and Dyachkovsky, 58 Eisch, 59 Jordan, 60 and Bochmann 61 showed that the activity of metallocene catalysts depends on the formation of cationic species. Today, most research groups agree with this statement.…”
Section: Activation Mechanismmentioning
confidence: 99%
“…Shilov and Dyachkovsky, 58 Eisch, 59 Jordan, 60 and Bochmann 61 showed that the activity of metallocene catalysts depends on the formation of cationic species. Today, most research groups agree with this statement.…”
Section: Activation Mechanismmentioning
confidence: 99%
“…Multinuclear NMR and solvent-polarity evidence support the conclusion that solvent-separated ion pairs (10) are the most active initiator of polymerization in the Cp 2 TiCl 2 /MeAlCl 2 catalyst system. [13,14] (11), in this system has been corroborated by its chemical capture with trimethyl(phenylethynyl)silane (12) as adduct 13, whose 3-D structure has been verified by single-crystal X-ray determination [Equation (5)]. [9] Eur.…”
Section: Introductionmentioning
confidence: 75%
“…Deuteriated solvents (Cambridge Scientific) for NMR measurements of oxygen-and moisture-sensitive substance were vacuum-transferred to the Schlenk glass vessels and stored over 4-Å molecular sieves under argon. Ϫ Nuclear magnetic resonance (NMR) spectra were recorded with Bruker AM 360 ( 4 Sn), external. Ϫ Gas chromatographic analysis (GC) was performed with a Hewlett-Packard Chromatograph, model 5880A, with helium as the carrier gas.…”
Section: Methodsmentioning
confidence: 99%
“…After dilution with dry diethyl ether, the lithium reagent was treated at 0°C with an ether solution of 10 mmol of dimethyltin dichloride. The reaction was stirred at reflux for 2 h and then poured into a solution of aqueous NH 4 Cl. Usual work-up gave an orange-yellow oil with the desired stannaindane as the major component by NMR criteria.…”
Section: ͱͱјϫBis(chlorodimethylstannyl)-o-xylene (32)mentioning
confidence: 99%
See 1 more Smart Citation